The unintended consequences of clinical trials regulations. - Alex D McMahon; David I Conway; Tom M Macdonald; Gordon T McInnes (PLoS Medicine, 2009)
Alex McMahon and colleagues critique the International Conference on Harmonisation (ICH) guidance on good clinical practice (GCP), arguing that it is having a disastrous effect on noncommerical randomized clinical trials in Europe.